Review of Chronic Inflammation and long term effects on health using Machine Learning Algorithms - Begum, Abeda; Kumar, Rajeev (International Journal of Computer Sciences and Engineering, 2021)
The purpose of this review is to find how today's generation impacted with chronic inflammation and its effects on health and long-term diseases using Machine Learning Algorithms. These diseases are found to be appeared after long time suffering with chronic inflammation. By detecting it early and taking lifestyle changes and healthy diet could potentially avoid the diseases like diabetes, cardiovascular diseases, cancer, arthritis, and bowel diseases. Autoimmune disease symptoms can be minimized by identifying inflammation levels and by taking precautionary measures at any stage of the patient. There are various inflammation markers to detect inflammation in the body by simple blood tests like CRP, ESR which are inexpensive and provide early disease detective mechanisms. These reports can be input to Machine Learning algorithms and train the system to help the patients to identify inflammation levels and alert them to take appropriate actions to prevent further damage from diseases on human organs.